Harmonizing Economic Principles, Islamic Values, and Entrepreneurial Attitudes for a Sustainable Environment - Ernandia Pandikar; Idrus Affandi; Disman Disman; Dadang Sundawa (Yupa: Historical Studies Journal)
The pressing environmental challenges of climate change, resource depletion, biodiversity loss, and pollution demand integrated solutions combining economic principles, Islamic values, and entrepreneurial attitudes. This study investigates how reorienting economic models to include environmental costs, guided by Islamic principles of stewardship (khalifah), balance (mizan), and justice (adl), can promote sustainability. It highlights the role of entrepreneurial innovation in developing sustainable technologies and business models. A qualitative methodology, including literature review and thematic analysis, aims to develop a conceptual framework that harmonizes these elements. By integrating green accounting, ethical teachings, and social entrepreneurship, this approach provides a comprehensive strategy for achieving a sustainable environment, supported by policy development, education, and community engagement.